GLIMSI: A real-world, multicenter study assessing the effectiveness and safety of Sitagliptin + Glimepiride + Metformin FDC in Indian patients with Type 2 diabetes - Zaveri, Kunal; Kulkarni, Girish; Nair, Rathish; Shanmugan, Govarthanan; Dharmadhikari, Shubhada Amol; Makkar, R. P. S.; Jalgaonkar, Rahul; Chatterjee, B. D.; Korukonda, Krishnaprasad; GLIMSI Investigator(s) Study Panel (PLOS ONE, 2026)
Background Type-2-diabetes-mellitus (T2DM), often linked to obesity, raises risk of microvascular and macrovascular complications. International guidelines recommend triple-therapy to reach haemoglobin A1c (HbA1c) targets when dual therapy fails to adequately control blood glucose levels. Sitagliptin, enhances glycaemic control by prolonging incretin action, boosting insulin secretion, and lowering glucagon levels. When combined with glimepiride and metformin this triple-therapy targets multiple mechanisms. This study evaluated the effectiveness and safety of this combination for improved T2DM management in Indian patients. Method This real-world, multicentre, observational chart review evaluated the efficacy and safety of a triple fixed-dose combination therapy in 1235 adult patients with T2DM across 194 clinical sites in India. Data were retrospectively extracted from patient records over a 12-week period. Descriptive and analytical statistics was applied for the study endpoints using SPSS ver. 29.0.1.0(171) and Microsoft Excel 2019. Result The study population had a mean age of 56.89 ± 10.29 years, with 64.70% reporting a family history of type 2 diabetes mellitus (T2DM). Smoking was identified as a prominent risk factor, affecting 38.65% of participants. Significant improvements were observed in glycemic parameters over 12 weeks: HbA1c levels decreased from 8.20 ± 0.60% to 7.08 ± 0.77% (p < 0.0001), fasting blood glucose (FBG) from 188.54 ± 47.59 mg/dL to 146.01 ± 41.53 mg/dL (p < 0.0001), and 2-hour postprandial plasma glucose (PPG) from 234.74 ± 50.40 mg/dL to 179.40 ± 42.51 mg/dL (p < 0.0001). Additionally, body weight significantly reduced from 75.99 ± 8.67 kg to 74.76 ± 9.07 kg (p < 0.0001). No significant safety concerns identified during the treatment period. Conclusion The triple-combination therapy (sitagliptin, glimepiride, and metformin) demonstrated superior efficacy in achieving glycemic control, as evidenced by significant reductions in HbA1c, fasting blood glucose (FBG), and postprandial plasma glucose (PPG). Furthermore, the therapy facilitated meaningful weight reduction, highlighting its clinical utility as a comprehensive therapeutic option for managing glycemic parameters in both T2DM with overweight and normal-weight patients.